Effect of Curcumin Natural Antioxidant on Oxidative Stability of Commercial Biodiesels from Different Raw Materials - Santos, Mikaelly Nayara; de Souza, Eliane Ferreira; Ramos, Talita Cuenca Pina Moreira; Cavalheiro, Alberto Adriano; Fiorucci, Antonio Rogério; da Silva, Margarete Soares (Orbital: The Electronic Journal of Chemistry, 2019)
Biodiesel emerges as an alternative biofuel for fossil ones because it is less polluting and can be produced from renewable sources. However, biofuels are generally more susceptible to auto-oxidation than fossil ones. Some fundamental characteristics in biofuel must be controlled in order to permit the correct operation of engines, so that the National Agency for Petroleum, Natural Gas and Biofuels (ANP) establishes specific resolutions about that. In most cases, the biofuel is poorly resistant to auto-oxidation, being required the addition of extrinsic antioxidant agents. In this work, it was demonstrated the curcumin is a natural product with excellent antioxidant behavior to be added to commercial biodiesel samples. The physical-chemical characteristics, induction period measured using Rancimat method EN14112 and acid number by ASTM D 664 method were investigated in present work for two commercial biodiesel samples prepared with different raw materials (soybean oil or soybean oil with beef tallow). The presence of beef tallow in one of the samples was positive for this biofuel quality in all of the aspects analyzed. Curcumin proved to be an efficient antioxidant for both biodiesel samples, increasing the induction period and reducing the acid number, guaranteeing good oxidative stability for commercial biodiesels studied. DOI: http://dx.doi.org/10.17807/orbital.v11i4.1225